Students’ Attitude toward A Non-Digital Game-Based Learning in English for Biology Course - Pratiwi, Andi Citra; Rahman, Ahmad Ardillah; Haris, Haris; Mar'ah, Zakiyah; Salsabila, Rughaya (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2023)
addresses the appeal of game-based learning for students. Despite the prevalence of game-based learning research, limited studies focus on non-digital approaches, particularly in English for Biology courses among English as a Foreign Language (EFL) learners in higher education settings. Accordingly, this quantitative descriptive study aims to fill the research gap by exploring undergraduate students' attitude towards non-digital game-based learning in an English for Biology course. The study, conducted at the Biology Education Department, Universitas Negeri Makassar, involves 64 students who experienced non-digital game-based learning through a collaborative word-guessing game. The research instrument utilized in this study was an attitude questionnaire which demonstrates high validity and reliability. Results of data analysis indicate an overall positive attitude (72.81%) among the students towards non-digital game-based learning, emphasizing enjoyment, motivation, retention, and engagement. Students' favorable disposition could be attributed to the unconventional learning atmosphere created by game elements, including rules, challenges, feedback, and rewards. The study suggests educators consider integrating non-digital game-based learning, fostering enjoyment, engagement, and retention, while emphasizing the importance of autonomy in promoting intrinsic motivation for positive learning outcomes.